2021
DOI: 10.3390/toxins13090662
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Degradation Kinetics of Patulin in Highly Acidic Conditions: Impact of Cysteine

Abstract: The thermal stability and degradation kinetics of patulin (PAT, 10 μmol/L) in pH 3.5 of phosphoric-citric acid buffer solutions in the absence and presence of cysteine (CYS, 30 μmol/L) were investigated at temperatures ranging from 90 to 150 °C. The zero-, first-, and second-order models and the Weibull model were used to fit the degradation process of patulin. Both the first-order kinetic model and Weibull model better described the degradation of patulin in the presence of cysteine while it was complexed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…There was a quick reduction in patulin concentration within the first 20 min in the presence of cysteine without ultrasound treatment ( p < .01), which was caused by the high concentration of cysteine. After 20 min, while no obvious difference was present in patulin degradation ( p > .05), which indicated that it was very difficult to further improve the degradation efficiency of patulin by cysteine without the help of ultrasound or heating processing under highly acidic conditions (Diao et al, 2021; Fliege & Metzler, 2000). A similar conclusion had been drawn that the sonolysis of azinphos‐methyl enhanced very quickly during the first 20 min and then it proceeded more slowly until 60 min (Agarwal et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was a quick reduction in patulin concentration within the first 20 min in the presence of cysteine without ultrasound treatment ( p < .01), which was caused by the high concentration of cysteine. After 20 min, while no obvious difference was present in patulin degradation ( p > .05), which indicated that it was very difficult to further improve the degradation efficiency of patulin by cysteine without the help of ultrasound or heating processing under highly acidic conditions (Diao et al, 2021; Fliege & Metzler, 2000). A similar conclusion had been drawn that the sonolysis of azinphos‐methyl enhanced very quickly during the first 20 min and then it proceeded more slowly until 60 min (Agarwal et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For the physical strategy, thermal processing is often considered for the degradation of patulin (Collin et al, 2008;Diao et al, 2021;Kokkinidou et al, 2014). However, patulin has a high resistance to heat under acidic conditions (Lovett & Peeler, 1973).…”
Section: Novelty Impact Statementmentioning
confidence: 99%
See 3 more Smart Citations